Unveiling the Effectiveness of Google Translate: A Health Text Translation Analysis - Kurniawan, Iwan; Suryawati, Sri Suci; Pradana, Satria Adi; Mulyadi, Rizqi Fitria; Aulia, Dina (English Education: Jurnal Tadris Bahasa Inggris, 2023)
There were difficulties faced by translators in translating text. Thus, because they found it difficult to translate and did not have a lot of vocabulary, they needed a translation tool such as Google Translate. Therefore, this research discussed the quality of the translation carried out by Google Translate in translating English text into Indonesian based on the theory of Rochayah Machali. The research methodology of this research was content analysis quantitative design. In this research, the population were texts about health from the Jakarta Post. The samples of the research were 32 Jakarta Post texts with the theme of health taken by simple random sampling. The instrument of this research was the rubric Rochayah Machali. After analyzing the data, it was found that from a total of 32 texts there were Google Translate abilities in the good category with 11 translations (34.375%), very good with 9 translations (28.125%), almost excellent with 7 translations (21.875%), fair with 3 translations (9,375). %), and bad category with 2 translations (6.25%). From the discussion above, it was concluded that Google Translate had a good translation with the highest score in the good category, namely 11 translations. The use of Google Translate was a solution for anyone to understand the text as a whole so it became a solution in understanding text in a foreign language, such as English